Sting, the scorpion man - Blade, Adam; Tucker, Ezra N. (Scholastic New York, 2010)
The Good beasts of Avantia have been imprisoned in the kingdom of Malvel the evil wizard. Tom has already fought five terrible Beasts and is nearing the end of his Quest. But in order to achieve victory, Tom must navigate through the tunnels under Malvel's castle, where Stin the Scorpion Man awaits